Co-development and Usability Testing of Research 101: A Patient-Oriented Research Curriculum in Child Health (PORCCH) E-Learning Module for Patients and Families - Walsh, Catharine M.; Jones, Nicola L.; McCreath, Graham A.; Connan, Veronik; Pires, Linda; Chen, Autumn Q. H.; Karoly, Aliza; Macarthur, Colin (Frontiers in Pediatrics, 2022)
Background: Engaging patients and families as research partners increases the relevance, quality, and impact of child health research. However, those interested in research engagement may feel underequipped to meaningfully partner. We sought to co-develop an online learning (e-learning) module, “Research 101,” to support capacity-development in patient-oriented child health research amongst patients and families. Methods: Module co-development was co-led by a parent and researcher, with guidance from a diverse, multi-stakeholder steering committee. A mixed-methods usability testing approach, with three iterative cycles of semi-structured interviews, observations, and questionnaires, was used to refine and evaluate the e-learning module. Module feedback was collected during testing and a post-module interview, and with the validated System Usability Scale (SUS), and satisfaction, knowledge, and self-efficacy questionnaires. Transcripts and field notes were analyzed through team discussion and thematic coding to inform module revisions. Results: Thirty participants fully tested Research 101, and another 15 completed confirmatory usability testing (32 caregivers, 6 patients, and 7 clinician-researchers). Module modifications pertaining to learner-centered design, content, aesthetic design, and learner experience were made in each cycle. SUS scores indicated the overall usability of the final version was “excellent.” Participants’ knowledge of patient-oriented research and self-efficacy to engage in research improved significantly after completing Research 101 (p<0.01). Conclusions: Co-development and usability testing facilitated the creation of an engaging and effective resource to support the scaling up of patient-oriented child health research capacity. The methods and findings of this study may help guide the integration of co-development and usability testing in creating similar resources.